ثقافة المنظمة ودورها في بناء الهوية التنظيمية للأساتذة بجامعة الشهيد حمه لخضر بالوادي - حاج بلقاسم، فرحات. محبوب، لزهر (جامعة الوادي university of eloued, 2018)
"تهدف هذه الدراسة إلى التعرف عن مساهمة ثقافة المنظمة في بناء الهوية التنظيمية للأستاذ الجامعي، وهدفت الدراسة أيضا إلى التعرف على:  واقع الثقافة التنظيمية داخل القسم.  مستوى الهوية التنظيمية لأساتذة قسم العلوم الاجتماعية.  هل يوجد فروق في استجابات الأساتذة نحو الهوية التنظيمية. ولتحقيق الهدف قمنا باستخدام الاستبيان كأداة رئيسية في جمع البيانات الاولية، وطبقت على عينة مسحية مكونة من 46 أستاذا بنسبة 73.01% من مجتمع الدراسة المكون من 63 أستاذا، وتم استخدام المنهج الوصفي التحليلي لإجراء الدراسة. توصلت الدراسة إلى النتائج التالية: • سيادة درجة مرتفعة للثقافة التنظيمية في القسم. • يتمتع الأساتذة بهوية تنظيمية قوية داخل القسم. • تساهم أبعاد الثقافة التنظيمية (القيم التنظيمية،الممارسات الإدارية، العلاقات الانسانية) في بناء الهوية التنظيمية (المركزية، التميز) بالقسم. • لا توجد فروق ذات دلالة إحصائية في مستوى الهوية التنظيمية للأساتذة وفقا لاختلاف الخصائص الشخصية (الجنس،العمر،الدرجة العلمية، التخصص، الخبرة). "The study aims to identify the contribution of the organizational culture in building the organizational identity of the university professor, It also aimed Identifying the reality of culture and the level of the organizational identity of the professors, and is there a differences in their response to organizational identity. To achieve the goal we have used the questionnaire as a data collection tool, And applied to a surveysample of 46 professors by 73.01% of the (63) members of the study population, and analytic descriptive approach have been used. The studyconcluded the followingresults: • High degree of organizational culture in the department. • Professors have a strongorganizationalidentity. • The dimensions of organizational culture (organizational values, management interactions, humanrelationships) contribute to building organizationalidentity (central, distinctive) in the department. • There are no significantstatisticaldifferences for professor in the field of the organizationalidentityaccording to personal variables differences (Sex, age, degree, specialty, experience).
دراسة ميدانية لعينة من الأساتذة بقسم العلوم الاجتماعية
مذكرة ماستر علوم إجتماعية تخصص علم الإجتماع تنظيم وعمل
Keywords: ثقافة المنظمة، الهوية التنظيمية، القيم التنظيمية، الممارسات الإدارية، العلاقات الانسانية; Culture organisationnelle, identité organisationnelle, valeurs organisationnelles, pratiques de gestion, relations humaines; Organizational culture, organizational identity, organizational values, management practices, human relations